2009
DOI: 10.1007/s00253-009-2316-x
|View full text |Cite
|
Sign up to set email alerts
|

Growth condition and bacterial community for maximum hydrolysis of suspended organic materials in anaerobic digestion of food waste-recycling wastewater

Abstract: This paper reports the effects of changing pH (5-7) and temperature (T, 40-60 degrees C) on the efficiencies of bacterial hydrolysis of suspended organic matter (SOM) in wastewater from food waste recycling (FWR) and the changes in the bacterial community responsible for this hydrolysis. Maximum hydrolysis efficiency (i.e., 50.5% reduction of volatile suspended solids) was predicted to occur at pH 5.7 and T = 44.5 degrees C. Changes in short-chain volatile organic acid profiles and in acidogenic bacterial comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…The clostridia are strict anaerobes and represent one of the most prevalent bacterial groups in biogas reactors. C. thermocellum and C. stercorarium were identified as the major players in the hydrolysis of plant biomass [41], whereas C. thermopalmarium was found to be the main butyric acid producer in a wastewater treatment system [42]. The clostridia represent the majority of the light-independent fermentative bacteria which have the ability to produce hydrogen [43].…”
Section: Resultsmentioning
confidence: 99%
“…The clostridia are strict anaerobes and represent one of the most prevalent bacterial groups in biogas reactors. C. thermocellum and C. stercorarium were identified as the major players in the hydrolysis of plant biomass [41], whereas C. thermopalmarium was found to be the main butyric acid producer in a wastewater treatment system [42]. The clostridia represent the majority of the light-independent fermentative bacteria which have the ability to produce hydrogen [43].…”
Section: Resultsmentioning
confidence: 99%
“…Since the organism among others is considered to play an important role in butyric and propionic acid production in the anaerobic digestion (Kim et al 2010), its appearance in the studied agricultural biogas systems was not too surprising. Since the organism among others is considered to play an important role in butyric and propionic acid production in the anaerobic digestion (Kim et al 2010), its appearance in the studied agricultural biogas systems was not too surprising.…”
Section: Clostridium Botulinummentioning
confidence: 99%
“…4). The high food-to-microorganism (F/M) ratio of 48 g COD/g VS allowed monitoring of acidogenesis prior to methane detection by 18.5 d. This F/M ratio is higher than a typical ratio of a biomethanation assay (Cho et al, 1995;McKeown et al, 2009) but ranges within the initial F/M ratios of an acidogenesis bioreactor reported in the literature (12.5-400 g COD/g VS) (Dareioti et al, 2014;Jung et al, 2015;Kim et al, 2010). During the batch period, COD and lipid concentrations remained unchanged (±5%); only a small fraction of the COD (3% of the initial) was converted to methane (Speece, 1996).…”
Section: Acidogenesis and Methanationmentioning
confidence: 84%